HDAC inhibitors improve CRISPR-Cas9 mediated prime editing and base editing - Nan Liu; Lifang Zhou; Guifeng Lin; Yun Hu; Yaoge Jiao; Yanhong Wang; Jingming Liu; Shengyong Yang; Shaohua Yao (Elsevier, 2022)
Recent advances in CRISPR-Cas9 techniques, especially the discovery of base and prime editing, have significantly improved our ability to make precise changes in the genome. We hypothesized that modulating certain endogenous pathway cells could improve the action of those editing tools in mammalian cells. We established a reporter system in which a small fragment was integrated into the genome by prime editing (PE). With this system, we screened an in-house small-molecule library and identified a group of histone deacetylase inhibitors (HDACi) increasing prime editing. We also found that HDACi increased the efficiency of both cytosine base editing (CBE) and adenine base editing (ABE). Moreover, HDACi increased the purity of cytosine base editor products, which was accompanied by an upregulation of the acetylation of uracil DNA glycosylase (UNG) and UNG inhibitor (UGI) and an enhancement of their interaction. In summary, our work demonstrated that HDACi improves Cas9-mediated prime editing and base editing.